Geotourism on XIII Koto Kampar: an Approach for Sustainable Eco-Geo System - Adi Suryadi; Tiggi Choanji; Yuniarti Yuskar; Nanda Natasia; Tristan Aulia Akhsan; M Revanda Syahputra (UIR PRESS, 2019)
XIII Koto Kampar has become one of the potential geotourism destinations in Riau Province. The beauty of geomorphological view of XIII Koto Kampar is the main attraction for tourism. This study aims to expose the uniqueness of geological conditions that form the geomorphological of study for educational, social and economic purposes. The method used for this study is a combination of geological and geomorphological mapping and assess the inventory of geosites. Geomorphological of study area is consist of wide lake with some islands on it. Based on the elevation, geomorphology of study area devided into four which are flatland, gentle hill, steep hill and very steep hill. The result of geological mapping shown there are two dominated rock claystone and sandstone. Geotourism potential of study area classified into three main zone namely geomorphological landscape zone, water play zone and waterfall zone. Sustainable system of geotourism of XIII Koto Kampar is potential livelihood to increase the economical of local society.